Correlation between task-based checklists and global rating scores in undergraduate objective structured clinical examinations in Saudi Arabia: a 1-year comparative study. - Khan, Uzma; Khan, Yasir Naseem (Journal of Educational Evaluation for Health Professions, 2025)
Purpose: This study investigated the correlation between task-based checklist scores and global rating scores (GRS) in objective structured clinical examinations (OSCEs) for fourth-year undergraduate medical students and aimed to determine whether both methods can be reliably used in a standard setting. Methods: A comparative observational study was conducted at Al Rayan College of Medicine, Saudi Arabia, involving 93 fourth-year students during the 2023-2024 academic year. OSCEs from 2 General Practice courses were analyzed, each comprising 10 stations assessing clinical competencies. Students were scored using both task-specific checklists and holistic 5-point GRS. Reliability was evaluated using Cronbach's α, and the relationship between the 2 scoring methods was assessed using the coefficient of determination (R²). Ethical approval and informed consent were obtained. Results: The mean OSCE score was 76.7 in Course 1 (Cronbach's α=0.85) and 73.0 in Course 2 (Cronbach's α=0.81). R² values varied by station and competency. Strong correlations were observed in procedural and management skills (R² up to 0.87), while weaker correlations appeared in history-taking stations (R² as low as 0.35). The variability across stations highlighted the context-dependence of alignment between checklist and GRS methods. Conclusion: Both checklists and GRS exhibit reliable psychometric properties. Their combined use improves validity in OSCE scoring, but station-specific application is recommended. Checklists may anchor pass/fail decisions, while GRS may assist in assessing borderline performance. This hybrid model increases fairness and reflects clinical authenticity in competency-based assessment.